Eudesman-Type Sesquiterpenoids from Stem Bark Dysoxylum gaudichaudianum and Cytotoxic Evaluation Against Human HeLa Cervical Cancer - Maira, Faizah; Naini, Al Arofatus; Mayanti, Tri; Farabi, Kindi; Fajriah, Sofa; Retnowati, Rurini; Supratman, Unang (Jurnal Kimia Valensi, 2025)
Two eudesmane-type sesquiterpenoids were isolated from the stem bark of Dysoxylum gaudichaudianum: 6α-hydroxy-eudesm-4(15)-en-1-one (1) and eudesm-4(15),7-dien-1β-ol (2). This study represents the first report of these compounds not only from D. gaudichaudianum but also from the genus Dysoxylum. The cytotoxic potential of two sesquiterpenoids was assessed against human cervical carcinoma (HeLa) cells employing the Resazurin-based PrestoBlue assay. Using cisplatin as a positive control, compound 1 exhibited moderate cytotoxicity with an IC₅₀ of 28.04 µM, whereas compound 2 showed comparatively weaker activity, with an IC₅₀ of 58.37 µM. Their structures were elucidated through comprehensive spectroscopic analyses, including HR-ESI-MS, ¹H NMR, and ¹³C NMR. Structure–activity relationship analysis indicates that hydroxylation at C-6 enhances cytotoxic activity, whereas the C-6/C-7 olefinic moiety reduces potency, likely due to increased molecular rigidity, highlighting key structural features for activity modulation in the eudesmane scaffold.